Effect of Application Massage Stimulation Method Endorphine, Oxytocin and Suggestiveness (SPEOS) on Breast Milk Production in Mothers Post Sectio Caesaria - Ayu Sugiartini, Ni Ketut; Rai Widiastuti, Ni Made; Ari Febriyanti, Ni Made; Deni Witari, Ni Nyoman (Jurnal MID-Z (MIDWIFERI ZIGOT), 2023)
Breast milk (ASI) is the best food that babies need in the first 6 months of life. WHO data (2016) shows that coverage of exclusive breastfeeding for babies aged 0-6 months worldwide is 39, while the target for exclusive breastfeeding is 50%. The inhibiting factor in breastfeeding is the production itself, especially in post-SC mothers. One effort that can be made to increase breast milk production is the SPEOS method. The aim of this research was to determine the effect of applying the Endorphine, Oxytocin and Suggestive Massage Stimulation (SPEOS) method on breast milk production in post-cesarean section mothers. This type of research is quasi-experimental with a post-test only control group design. The number of samples used in this research was 30 respondents consisting of 15 control groups and 15 intervention groups. The results of the study showed that the average breast milk production in SC mothers who were given the SPEOS method was 37.67 ml higher than in post-SC mothers who were not given the SPEOS method, namely only 19.44 ml. Statistical tests showed that there was an effect of applying the Endorphin, Oxytocin, Suggestive Massage Stimulation (SPEOS) method on breast milk production (p-value=0.000). It is hoped that the SPEOS method can be used as an alternative option in managing increasing breast milk production, because the SPEOS method has been proven to be effective in increasing breast milk production.